STUDY OF FRESHWATER LOBSTER (Cherax quadricarinatus) FLOUR CHARPAS FLOUR FORMULATION ON CONSUMER ACCEPTANCE - Dedi Arisandi; Desmelati Desmelati; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
AbsctractThis study aimed to determine the effect of the formulation of freshwater carapace flour crackers (Cherax quadricarinatus) on consumer acceptance of the crackers produced. This study used experimental methods. The experimental design used was a complete non-factorial randomized design with four levels of treatment, namely D0 (without the addition of carapace flour), D1 (addition of 5% carapace flour), D2 (addition of 10% crayfish carapace flour), D3 (addition of 15% crayfish carapace flour). The tested parameters were organoleptic tests (taste, appearance, aroma, and texture), and flower power tests. The results showed that the addition of carapace flour (Cherax quadricarinatus) had a significant effect on organoleptic quality (taste, appearance, aroma, texture) with the D2 treatment being the best treatment because it was preferred by the panelists. Meanwhile, based on the flower power, D0 was the best treatment with a D0 value of 0.63 cm.Keywords: by product, crackers, flour, freshwater lobster carapace .